Prevalence and related factors of abdominal obesity among urban adults aged 35 to 79 years in southwest China - Huang, Chuan; Zhang, Ying; Liu, Ya; Liu, Jian-Xiong; Hu, Yong-Mei; Tang, Wei-Wei; Wang, Tzung-Dau; Huang, Xiao-bo (Frontiers in Public Health, 2023)
Objectives This study aimed to investigate the prevalence and related factors of abdominal obesity among urban adults aged 35 to 79 years in southwest China. Methods From September 2013 to March 2014, a multi-stage sampling was conducted, and a total of 10981 people aged 35-79 years living in Chengdu and Chongqing were included. More than 30 investigators were trained in data collection, including questionnaire, anthropometric measurements and blood biomarkers testing. Abdominal obesity was defined as waist circumference ≥ 90 cm for men and ≥ 85 cm for women. ResultsThe prevalence of abdominal obesity was 30.7%, 24.8% in males and 33.9% in females (P < 0.001). The prevalence of abdominal obesity increased with BMI . The prevalence of abdominal obesity was positively correlated with age, sex, marriage, alcohol consumption, hypertension and diabetes, and negatively correlated with high education level, smoking and Physical activity. Conclusions The prevalence of abdominal obesity among adults aged 35-79 in urban communities in southwest China is high, which is close to that of adults in urban communities in China. We should strengthen health education among the population, adopt healthy diet, maintain moderate physical activity and other measures to curb the prevalence of abdominal obesity in urban communities in southwest China.